A strategy for synthesis of lipid nanoparticles using microfluidic devices with a mixer structure. Issue 57 (25th June 2015) - Maeki, Masatoshi; Saito, Tatsuyoshi; Sato, Yusuke; Yasui, Takao; Kaji, Noritada; Ishida, Akihiko; Tani, Hirofumi; Baba, Yoshinobu; Harashima, Hideyoshi; Tokeshi, Manabu
<x xml:space="preserve">Abstract</x> Formation behavior was discussed for lipid nanoparticles (LNPs) in the microfluidic devices equipped with different cycle numbers of the micromixers.